2019
DOI: 10.1016/j.jpain.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The (Parental) Whole Is Greater Than the Sum of Its Parts: A Multifactorial Model of Parent Factors in Pediatric Chronic Pain

Abstract: Parents play a critical role in children,s experience of, and recovery from, chronic pain. Although several parental factors have been linked to child pain and functioning, these factors are typically examined in isolation or as moderators or mediators. Structural equation modeling affords the opportunity to examine the extent to which parental factors are interrelated, and if there are differential associations among parental factors and child outcomes. Based on extant literature, a unified model of parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Parents' chronic pain, emotional distress and responses to their child's pain play a pivotal role for this familial transmission (Stone & Wilson, 2016). In line with previous studies (Hechler et al, 2011;Law et al, 2017;Wilson, Moss, Palermo, & Fales, 2014), Cordts, Stone, Beveridge, Wilson, and Noel (2019) found that parental pain-related catastrophizing -the tendency to highly focus on child pain, to magnify the threatening value of pain (Stone & Wilson, 2016) -was impactful on child pain and functioning. Behavioural responses such as solicitousness (positive reinforcement of child pain behaviours; Noel et al, 2015) are also associated with worsened child pain outcomes (Connelly, Bromberg, Anthony, Gil, & Schanberg, 2017;Hechler et al, 2011;Law et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Parents' chronic pain, emotional distress and responses to their child's pain play a pivotal role for this familial transmission (Stone & Wilson, 2016). In line with previous studies (Hechler et al, 2011;Law et al, 2017;Wilson, Moss, Palermo, & Fales, 2014), Cordts, Stone, Beveridge, Wilson, and Noel (2019) found that parental pain-related catastrophizing -the tendency to highly focus on child pain, to magnify the threatening value of pain (Stone & Wilson, 2016) -was impactful on child pain and functioning. Behavioural responses such as solicitousness (positive reinforcement of child pain behaviours; Noel et al, 2015) are also associated with worsened child pain outcomes (Connelly, Bromberg, Anthony, Gil, & Schanberg, 2017;Hechler et al, 2011;Law et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…Parents differ in pain-related catastrophizing and solicitousness (Frerker, Hirschfeld, Thielsch, & Hechler, 2018). However, the vast majority of studies have focused on the impact of parental responses on child outcomes (Connelly et al, 2017;Cordts et al, 2019;Hechler et al, 2011;Higgins et al, 2015;Hoftun et al, 2013;Law et al, 2017;Stone, Bruehl, Smith, Garber, & Walker, 2018;Stone & Wilson, 2016;Wilson et al, 2014), rather than investigating modulating factors. Modulating factors may be subdivided into top-down and bottom-up processes (Goubert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of parenting behaviors on the functioning of youth with chronic pain is well-established, 16 and research suggests parents' mental health and physical health are also related to children's chronic pain outcomes. 10 , 12 , 19 , 26 , 32 , 42 , 47 However, adverse childhood experiences (ACEs) among parents of youth with chronic pain have not been examined.…”
Section: Introductionmentioning
confidence: 99%